1965
DOI: 10.1111/j.2042-7158.1965.tb07608.x
|View full text |Cite
|
Sign up to set email alerts
|

The action of arsenic on Bacillus cereus

Abstract: Sodium arsenite (0–4 mm) inhibited the growth of exponentially growing Bacillus cereus, whereas sodium arsenate was growth‐inhibitory only at 10 mm concentration. When the phosphate concentration was reduced sharply, 3.3 mm sodium arsenate inhibited growth, whereas the inhibitory effect of arsenite was independent of phosphate concentration. Neither arsenite nor arsenate produced any specific effects on the incorporation of precursors into ribonucleic and deoxyribonucleic acids, protein or cell wall, in suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In both cases, the resistant bacteria contained less drug than did the sensitive ones (Connamacher et al 1967;Mandel et al 1965). In the author's experience, the recovery from both compounds must occur within 3 hr or not at all.…”
Section: Interrelationships Between the Mechanisms Of Resistance And mentioning
confidence: 78%
See 2 more Smart Citations
“…In both cases, the resistant bacteria contained less drug than did the sensitive ones (Connamacher et al 1967;Mandel et al 1965). In the author's experience, the recovery from both compounds must occur within 3 hr or not at all.…”
Section: Interrelationships Between the Mechanisms Of Resistance And mentioning
confidence: 78%
“…Because both tetracycline (Jones & Morrison, 1962) and arsenite (Mandel et al 1965) have been shown to interrupt the energy production of the cell, other energy inhibitors and active transport inhibitors were tested for reversible bacteriostatic action. Ouabain (IO-~ M) did not inhibit Bacillus cereus, nor was bacterial inhibition observed with up to I O -~ M-phloridzin, 2,4-dinitrophenol, ethionine, potassium fluoride, amobarbital, or malonic acid.…”
Section: Cross-resistance Between Tetracycline and Other Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few reports are available on the effect of phosphate on both As(II1) and As(V) toxicity, and the relationship of phosphate concentration to the toxicities is confused because different taxa respond differently. As with C. parvula, the toxicity of As(II1) to the bacterium Bacillus cereus was independent of phosphate concentration, but the toxicity of As(V) could be increased by lowering the phosphate concentration [7]. However, in some fungi, phosphate concentration affects the toxicity of both As(II1) and As(V) [8].…”
Section: Resultsmentioning
confidence: 94%